Trade concentration and crisis spillover: Case study of transmission of the subprime crisis to Thailand - Kornkarun Cheewatrakoolpong; Somprawin Manprasert (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2012)
The threat of the subprime crisis in the United States began to make itself felt in early 2008, with its effects subsequently become global. It is evident that trade linkages have been the most important channel for transmitting the subprime crisis to East Asian countries, including Thailand. The international trade literature points out that trade concentration is considered to be an important factor in the amplification of the effects of the crisis. Thailand was still greatly affected by the recent crisis even though its direct exports to the G3 markets, i.e., the United States, the European Union and Japan, has been declining during the past 40 years. In fact, international trade linkages could be both directly and indirectly linked through international supply chain production. In this paper, the authors attempt to measure the importance of total trade concentration, which includes the effects through indirect linkages, and its connection to the transmission of external shocks experienced by the Thai economy. By constructing an algorithm that calculates total trade linkages, the authors find that Thailand still has high exposure to the G3 markets. Simulation using the CGE model has also confirmed that the country was, in fact, seriously affected through indirect channels. The results also show that the high concentration of domestic forward linkages in certain areas leads to those industries accumulating the effects of external shocks from financial crisis.
Keywords: F14; F41; F42; 330; trade concentration; crisis transmission; export diversification; backward linkages; financial crisis; Finanzmarktkrise; Subprime-Hypothek; Außenwirtschaft; Exportdiversifizierung; USA; Thailand